2005
DOI: 10.1002/mus.20368
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in mitochondrial myopathy: A randomized controlled trial

Abstract: Patients with mitochondrial myopathies (MM) usually suffer from exercise intolerance due to their impaired oxidative capacity and physical deconditioning. We evaluated the effects of a 12-week supervised randomized rehabilitation program involving endurance training in patients with MM. Twenty MM patients were assigned to a training or control group. For three nonconsecutive days each week, patients combined cycle exercise at 70% of their peak work rate with three upper-body weight-lifting exercises performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 32 publications
2
54
0
Order By: Relevance
“…Endurance exercise training has also been found to be safe and improve peak exercise tolerance and cardiac and skeletal muscle function in conditions that share similar characteristics as BTHS: mitochondrial myopathies (Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009 and congestive heart failure (Coats et al 1992;Delagardelle et al 2002;Giannuzzi et al 2003;Bartlo 2007). In patients with other mitochondrial myopathies, an endurance exercise program (3-5Â/week, 12 weeks, 70% VO 2peak ) increased peak oxygen consumption 23-29% and peak work rate 16-100% (Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009. Also, 14 weeks of endurance exercise training increased peak oxygen consumption (~25%), peak skeletal muscle oxygen extraction (20%), and mitochondrial function, enzyme activity and volume (~50%) without an improvement in cardiac function in individuals with mitochondrial myopathies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endurance exercise training has also been found to be safe and improve peak exercise tolerance and cardiac and skeletal muscle function in conditions that share similar characteristics as BTHS: mitochondrial myopathies (Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009 and congestive heart failure (Coats et al 1992;Delagardelle et al 2002;Giannuzzi et al 2003;Bartlo 2007). In patients with other mitochondrial myopathies, an endurance exercise program (3-5Â/week, 12 weeks, 70% VO 2peak ) increased peak oxygen consumption 23-29% and peak work rate 16-100% (Cejudo et al 2005;Jeppesen et al 2006Jeppesen et al , 2009. Also, 14 weeks of endurance exercise training increased peak oxygen consumption (~25%), peak skeletal muscle oxygen extraction (20%), and mitochondrial function, enzyme activity and volume (~50%) without an improvement in cardiac function in individuals with mitochondrial myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Endurance exercise training has been shown to improve subjective quality of life in non-BTHS heart failure (Tyni- Lenne et al 1996;Belardinelli et al 1999;Taylor et al 2014) and mitochondrial myopathy (Cejudo et al 2005). In the current study, endurance exercise training did not significantly improve overall (i.e., total score of the Minnesota Living with Heart Failure Questionnaire) subjective quality of life but did significantly improve scores on specific questions related to dyspnea and side effects of heart failure treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, recent studies on patients with different types of muscle disease have demonstrated the beneficial effects of aerobic training on exercise performance and in terms of improved quality of life Orngreen et al 2005). Benefits of aerobic exercise training on blood lactate kinetics, muscular strength, oxygen consumption and endurance performance have also been demonstrated in MD patients (Cejudo et al 2005). This benefits are thought to be a consequence of modifications in the utilization rate of fuels for oxidative metabolism during exercise, with a reduction in muscle lactate production and respiratory change ratio (Mac Rae et al 1995).…”
Section: Application Of Functional Diagnostic Techniques To Assess Efmentioning
confidence: 97%
“…It is of interest that a mild, low-volume exercise-training program using patients with a variety of mitochondrial enzyme defects resulted in significant improvements inVo 2 max, muscle strength and endurance, maximal heart rate, respiratory rate, and VE, and in reducing the lactacidosis (37,297). Therefore, regular exercise appears to have resulted in the improved activities of many enzymes in the respiratory chain in heart, respiratory and skeletal muscles, consistent with the hypothesis that these individuals also suffer from diminished oxidative capacity due to chronic inactivity.…”
Section: Mitochondrial Enzyme Abnormalitiesmentioning
confidence: 99%